Impact of leukemia subtype and demographics on patient quality of life in 76 countries: a cross-sectional study - Salek, Sam; Nier, Samantha; Pemberton-Whiteley, Zack; Ionova, Tatyana; Ianni, Giuseppe; Tripepi, Giovanni; York, Nick; Schroeter, Nicole; Huntley, Kathryn; Rynne, Michael; Costello, Denis; Pecova, Lidija; et al. (Frontiers in Hematology, 2025)
BackgroundDisease-specific factors associated with decreased quality of life (QoL) in patients with leukemia have not been studied in a large-scale, global, observational study.MethodsThis cross-sectional study used the validated Hematological Malignancy Patient Reported Outcomes (HM-PRO) questionnaire to assess the impact of leukemia subtype, age, sex, and years living with the disease on QoL of patients with leukemia.ResultsOverall, 2,628 patients responded: 45.7% had chronic lymphocytic leukemia (CLL), 34.0% had chronic myeloid leukemia (CML), 11.8% had acute myeloid leukemia (AML), and 3.5% had acute lymphoblastic leukemia (ALL). HM-PRO scores differed significantly between leukemia subtypes (p<0.001); patients with ALL reported the worst outcomes. Women had significantly worse scores than men (p<0.001). HM-PRO scores were inversely correlated both with age (ρ= –0.24, p<0.001) and years living with the disease (ρ= –0.14, p<0.001).ConclusionPatients reported the greatest concerns over their future treatment and future health, as well as concerns over dying and being a burden to others. Patients need access to support services, such as the availability of a clinical psychologist as part of the hematology team, to provide support with the emotional aspects of a leukemia diagnosis, especially for patients with acute leukemia subtypes reporting the lowest mean QoL scores.